2020
DOI: 10.3390/app10082980
|View full text |Cite
|
Sign up to set email alerts
|

Mandible Integrity and Material Properties of the Periodontal Ligament during Orthodontic Tooth Movement: A Finite-Element Study

Abstract: We used the finite-element method (FEM) to investigate the effects of jawbone model integrity and the material properties of the periodontal ligament (PDL) on orthodontic tooth movement. Medical imaging software and computer-aided design software were used to create finite-element models of a partial and complete mandibles based on dental cone beam computed tomography images of the human skull. Additionally, we exerted an orthodontic force on the canine crown in the direction of an orthodontic miniscrew under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…that describe physical behavior upon the application of an external load (e.g., mastication forces, an orthodontic force, etc.) or upon position modification [7]. All individual elements are connected by nodes that form a coherent network.…”
Section: Introductionmentioning
confidence: 99%
“…that describe physical behavior upon the application of an external load (e.g., mastication forces, an orthodontic force, etc.) or upon position modification [7]. All individual elements are connected by nodes that form a coherent network.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have signaled the opportunity to use this method of investigation both in orthodontics and in implantology or prosthetic rehabilitation [1,2]. This justifies the in-terest shown by specialists in the field of dentistry to achieve mathematical models capable of simulating the evolution of medical processes such as stress variation in the enamel and dentin in restorative dentistry [3], assessment of implant prosthetic rehabilitation in mandibular bone atrophy [4], prediction of the endodontic treatment outcome [5], finite element study during orthodontic treatment [6] and stress in the periodontal ligament as a result of orthodontic treatment in association with periodontal disease [7]. Finite element analysis is a useful method with effective results in determining the effects of orthodontic forces during orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the FE studies on clear aligners are limited to a single tooth, or at times, a segment of the dental arch and only a few have established complete dental arch models. Previous research has shown that the extension of the segment included in the analysis influences, although to a small degree, the biomechanical response of the PDL [33].…”
Section: Discussionmentioning
confidence: 99%
“…is is most likely caused by a difference in boundary condition settings [33]. However, in our analysis, a large area was modelled, and the boundary conditions were applied farther from the tooth that needs to be moved.…”
Section: Discussionmentioning
confidence: 99%